Biological Identity of Nanoparticles In Vivo: Clinical Implications of the Protein Corona. Issue 3 (March 2017) - Caracciolo, Giulio; Farokhzad, Omid C.; Mahmoudi, Morteza
Abstract : Despite the advances in biomedical applications of nanoparticle (NP) and numerous publications, few NPs have made it to clinical trials and even fewer have reached clinical practice. This wide gap between bench discoveries and clinical applications is mainly because of our limited understanding of the biological identity of NPs. In physiological environments, NPs are coated by a 'protein corona' (PC), critically affecting physiological and therapeutic responses. To date, nearly all studies attempting to characterize the PC have been conducted in vitro . Here, we review recent advances in our understanding of the in vivo PC . We also discuss recent developments of quantitative models to predict biological interactions and how they offer new opportunities for the clinical translation of NPs. Trends: Nanoparticles (NPs) are increasingly considered promising new medical tools, but their clinical application remains limited. In living systems, NPs are exposed to high protein concentrations, leading to the formation of a protein corona (PC) that mediates interactions between the NPs and the biological environment. The rational development of NPs for clinical applications requires a deep understanding of the biological effects triggered by the PC in vivo . Establishing structure–activity relations linking NP properties and PC fingerprints to physiological responses is needed for effective biomedical applications of NPs. Improving the ability to predict the biological outcomes of NPs will speed up their translation to the clinic.